ACP-EEC Convention of Lomé signed on 28 February 1975 and related documents (Office for Official Publications of the European Communities LuxembourgLU, 1975)
Consistat of 7 titles which deal, inter alia with trade cooperation; export earnings from commodities; industrial cooperation; financial and technical cooperation; provisions relating to establishment, services, payments and capital movements. Provides details of the Institutions of the Convention viz. Council of Ministers assisted fy the Committee of Ambassadors, and the Consultative Assembly.
Located in the Office of the Secretary-General